Pelatihan Pembelajaran Terdiferensiasi Untuk Meningatkan Kompetensi Guru Sekolah Indonesia Kota Kinabalu - Fikrianto, Misbah (CV. Multi Kreasi Media, 2024)
Increasing teacher competency must be carried out continuously. Teachers are an important component in implementing learning. In the Merdeka curriculum, the term Differentiated Learning is known. Differentiated learning is learning that recognizes students' differences in terms of interest, readiness to learn and motivation. Differentiated learning maximizes learning according to students' abilities. In differentiated learning, students are given assignments according to their abilities, interests and preferences, so that they can maximize their potential which leads to increased learning outcomes and motivation. Differentiated Learning Training was carried out at the Kota Kinabalu Indonesian School with 20 teachers participating. This activity provides benefits for teachers at the Kota Kinabalu Indonesian School (SIKK). Differentiated learning also builds cooperation between students and increases their independence in learning. The training was held for 3 days from July 31 to August 2 2024. Training participants received 90% satisfaction with the material. The implementation of this training strengthens the quality of teachers and the school ecosystem.